2019
DOI: 10.1080/21580103.2019.1620135
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, soil characteristics and carbon stock of the regenerating banj oak forests in Almora, Central Himalaya

Abstract: The present study is aimed to study regeneration status, population structure, soil characteristics and carbon stock of seven regenerating banj oak (Quercus leucotrichophora) forests in the central Himalaya. The phytosociological study was done by using ten 10 m  10 m quadrat at each site. Biomass and carbon stock of trees were calculated by using regression equations. Soil samples were collected from three depths (0-10, 10-20 and 20-30 cm) by using soil corer. The tree density of two most dominant species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…The basal area recorded in study stands (5.2-88.39 m 2 ha À1 ) is either comparable or greater than the values reported for other oak forests in central Himalaya (Rawat & Singh, 1988;Verma & Garkoti, 2019). The study clearly illustrated that the stand and A. nepalensis basal area were strongly correlated with the stand carbon stock (Figure 6).…”
Section: Change In Ecosystem Carbon Stocksupporting
confidence: 71%
“…The basal area recorded in study stands (5.2-88.39 m 2 ha À1 ) is either comparable or greater than the values reported for other oak forests in central Himalaya (Rawat & Singh, 1988;Verma & Garkoti, 2019). The study clearly illustrated that the stand and A. nepalensis basal area were strongly correlated with the stand carbon stock (Figure 6).…”
Section: Change In Ecosystem Carbon Stocksupporting
confidence: 71%
“…However, Law et al (2001) argued the opposite of this situation. Verma et al (2019) reported that N concentration and TN stock increased with an increase in tree diameter and tree density.…”
Section: Litter On the Forest Floor And Soil Organic Carbonmentioning
confidence: 99%
“…, 2013;Berenguer et al, 2014;Biswas et al, 2020;Saimun et al, 2021). The variation of living tree carbon stock among the forests with different vegetation compositions is more or less supported byIkraoun et al (2022),Poudel et al (2020),Sharma et al (2020),Verma and Garkoti (2019),Shrestha et al (2016),Aryal et al (2013) andJoshi et al …”
mentioning
confidence: 89%